2008
DOI: 10.1128/jb.01525-07
|View full text |Cite
|
Sign up to set email alerts
|

Study of Anoxic and Oxic Cholesterol Metabolism by Sterolibacterium denitrificans

Abstract: The initial enzymes and genes involved in the anoxic metabolism of cholesterol were studied in the denitrifying bacterium Sterolibacterium denitrificans Chol-1ST . The second enzyme of the proposed pathway, cholest-4-en-3-one-⌬ 1 -dehydrogenase (AcmB), was partially purified. Based on amino acid sequence analysis, a gene probe was derived to screen a cosmid library of chromosomal DNA for the acmB gene. A positive clone comprising a 43-kbp DNA insert was sequenced. In addition to the acmB gene, the DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 37 publications
1
80
0
2
Order By: Relevance
“…Recently, the initial reactions involved in the anaerobic metabolism of cholesterol and testosterone were reported (19)(20)(21), albeit the ring cleavage details of the anaerobic pathways are yet to be unraveled. In this study, we adopted a 13 C metabolomic approach to investigate the anaerobic degradation of testosterone using S. denitrifi cans as a model organism.…”
mentioning
confidence: 99%
“…Recently, the initial reactions involved in the anaerobic metabolism of cholesterol and testosterone were reported (19)(20)(21), albeit the ring cleavage details of the anaerobic pathways are yet to be unraveled. In this study, we adopted a 13 C metabolomic approach to investigate the anaerobic degradation of testosterone using S. denitrifi cans as a model organism.…”
mentioning
confidence: 99%
“…In a previous investigation, AcmA was identified as an NAD ϩ -dependent enzyme belonging to the short-chain dehydrogenase/reductase family (31). Here, we showed that AcmA is a periplasmic protein.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 55%
“…The existence of free NAD(P) ϩ in the periplasm seems unlikely for various reasons (53), although there is no direct experimental evidence regarding this matter. The primary structure of AcmA is highly similar to that of 3␤-hydroxysteroid dehydrogenase isolated from various bacteria, including Comamonas testosteroni (31). The 3␤-hydroxysteroid dehydrogenase of C. testosteroni (formerly named Pseudomonas testosteroni (54)) was also reported to be a periplasmic protein (55).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 71%
See 2 more Smart Citations